Assessment of Soil Erosive Fragility Using Cross Mapping with Support of the Geographic Information System in the Municipality of São Francisco de Assis/RS/Brazil - Oliveira, Mariana Xavier de; Trentin, Romario; Robaina, Luis Eduardo de Souza (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2019)
The present study analyzes factors that condition the occurrence of erosive incisions in the municipality of São Francisco de Assis, located in the western region of Rio Grande do Sul, in the Ibicuí river basin. Multicriteria analysis with GIS support was used for the development of map algebra operations. The base maps for the definition of the map of erosive fragility were slope, soils, lithology and land use, with weights assigned to each of the variables present in the base maps. The mapping of erosive fragility was carried out by the map algebra operation carried out in the GIS, using the Raster Calculator tool. The areas with the lowest erosive fragility, occur in the NW portion of the municipality, and are related to the occurrence of natural tree vegetation. In the municipality, areas with medium erosive fragility occur at the extreme NE-E and NW, formed by soils on volcanic rocks or sandstone with volcanic contribution where the predominant uses agricultural. The occurrence of very high erosive fragility is associated with the substrate of sandstones, friable soils and low soil cover. The work showed the importance of the multi-criteria relationship involving physical attributes of the landscape and the study of land use is essential in studies of fragility and environmental potential.